Tradução, adaptação e validação da UCLA Loneliness Scale(version 3) para o português do Brasil em uma amostra de idosos - Tatiane Prette Kuznier (2016)
The feelings of loneliness have serious consequences on the health ofthe elderly, making them more susceptible to depressive symptoms, the decline in mental health and is associated with increased mortality and suicidal ideation. It is necessary to know about the loneliness level experienced by the elderly, so that strategies to reduce or improve this condition can be implemented. One way to measure loneliness level is the use of scales. As scales were not found in Brazil that mensurassem loneliness in the elderly, it was decided in this study the use of theUCLA Loneliness Scale, originally built in the United States. Objective: To perform the translation, cultural adaptation and validation of the UCLA Loneliness Scale (version 3) in a sample of Brazilian elderly. Method: This is a methodological study, carried out in two stages: the first was the translation and cultural adaptation of the English language version of the UCLA Loneliness Scale (version 3) for the Portuguese version of Brazil; in the second stage it was carried out to study the validity of the scale. The adaptation process was carried out through the following steps: initial translation, synthesis of translations, back-translation, judges Committeeand Pre-test. Construct validity was analyzed by comparing different groups for the convergent construct validity and the exploratory factor analysis. The sample used for scale validation consisted of 136 elderly. To assess the construct validity by comparing between different groups was performed t test to compare possible differences in the measurements of the UCLA Loneliness Scale (Version 3) BR, sexand marital status. To evaluate the convergent construct validity were performed Pearson correlation test between UCLA and measure social support measures and depression. The strength of the correlations were analyzed according to the classification values below 0.1 were classified as null correlation between 0.1 and 0.3 as weak intensity correlation between 0.4 and 0.6, as moderate and values from 0.7 to 1 in intense correlation. Construct validity was evaluated by factor analysis. theadequacy of measurement test were used sample of Kaiser-Meyer-Olkin (KMO) and Bartlett's test of sphericity. Regarding the retention factor was used eigenvalues> 1. The extraction of factors was performed from a principal component analysis and Varimax rotation. Reliability was calculated by Cronbach's alpha, and the values considered acceptable when present in the range 0.70 to 0.90. The significance level was 0.05. Results: of the survey participants, 57.3% had a companion (a), with amean age of 70.33 years. The mean duration of formal study was 4.01 years. The 11 average income was R $ 1,172.68, most met retired (58.5%), 57.4% claimed to have white skin. The predominant religion was Catholic (79.4%). The average number of children was 4.23, 30.1% said living with his companion (a) and 20.6% reported living alone. The elderly, 89.7% claimed to have a disease, and 74.3% reported beinghypertensive and 33.1%, diabetic. The results obtained by the UCLA Loneliness Scale (Version 3) BR, indicated an average value of solitude of 36.86 points. The score for the presence or absence of depressive symptoms varied between 1 and 58 points, averaging 18.63 points. Regarding social support, the overall average was 83.30 points. There was no statistically significant difference between the measure ofloneliness and sex (t = 0.915, p = 0.362) and between the measure of loneliness and marital status (t = 1, 940, p = 0.054). There was a significant positive correlation of moderate intensity between loneliness and depression measures (r = 0.665; p = 0.001) and a significant negative correlation of moderate intensity between lonelinessmeasures and social support (r = -0.576; p = 0.001). Regarding the exploratory factor analysis, as Kaiser-Meyer-Olkin (KMO) indicated an adequate sample size for the stability of the factorial structure (KMO = 0.86), the Bartlett test was statistically significant (2 (190) = 929.47, p <0.001) and the best factor solution was the extraction of a single factor. The reliability was obtained an appropriate value for the internal consistency of the UCLA Loneliness Scale (Version 3) BR ( = 0.88).Conclusion: The method used to perform the translation and cultural adaptation process was considered relevant and appropriate, since it allowed the adequacy of the scale for the Brazilian elderly population, including a clear and easily understood by the participants language. The UCLA Loneliness Scale (Version 3) BR showed no difference in solitude measure based on sex. Regarding marital status, there was nodifference of loneliness level among the elderly who have and those who do not have companions. The convergent validity was confirmed by the values of solitude measure of correlation coefficients with the measures of social support and depression. Through factor analysis, we observed the presence of a single factor, demonstrating the one-dimensionality of the scale. The instrument presented appropriate value of Cronbach's alpha. As the Brazilian version of the Loneliness Scale UCLA (version 3) BR a valid and reliable instrument, it is recommended its useas an assessment tool of loneliness among elderly Brazilians.